THEORETICAL STUDY OF THE ECCENTRIC-TYPE EXPERIMENTAL VACUUM VALVE DESIGN - Lazizbek Mekhmonaliev (European Science Publishing, 2025)
This article theoretically analyzes the shortcomings observed during the operation of SS-15 type separators used in the cotton-cleaning industry, particularly the energy losses caused by air leakage into the vacuum valve system and its impact on the quality of raw cotton. Furthermore, an experimental eccentric-type vacuum valve design was developed, and its efficiency was analyzed with respect to angular velocity, number of blades, and inclination angle.
Keywords: Separator, pneumatic transport system, raw cotton, energy efficiency, experimental design, eccentric vacuum valve, blade angle, filling coefficient.